1990
DOI: 10.1016/0014-5793(90)81059-w
|View full text |Cite
|
Sign up to set email alerts
|

The three carboxy‐terminal amino acids of human interleukin‐6 are essential for its biological activity

Abstract: We have constructed on the cDNA level deletion mutants of human interleukin-6 lacking one, two, three or four amino acids from the carboxyterminus of the molecule. After in vitro transcription and translation the biological activity of these deletion mutants was determined by two independent bioassays. Both, the mouse B9 cell proliferation assay and the fibrinogen induction assay with the human hepatoma cell line HepG2 led to the following result: already the removal of the last amino acid resulted in a five-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 14 publications
2
23
0
1
Order By: Relevance
“…These results suggest that interactions involving the C-terminal amino acids stabilize the tertiary structure of mIL-6 and that the Ala-183, Leu-184, and Met-187 residues in pMC5H are more efficient in this respect than their counterparts in mIL-6 (Ser-183, Thr-184, Thr-187). Both Met-187 and Leu-I84 have been suggested to be of particular importance for receptor binding in hIL-6 (Kriittgen et al, 1990b;Yasueda et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that interactions involving the C-terminal amino acids stabilize the tertiary structure of mIL-6 and that the Ala-183, Leu-184, and Met-187 residues in pMC5H are more efficient in this respect than their counterparts in mIL-6 (Ser-183, Thr-184, Thr-187). Both Met-187 and Leu-I84 have been suggested to be of particular importance for receptor binding in hIL-6 (Kriittgen et al, 1990b;Yasueda et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal amino acids of hIL-6 have been shown to be essential for bioactivity. The removal of three C-terminal residues causes a drastic reduction of bioactivity (Kriittgen et al, 1990b). Without structural information, it is difficult to ascertain from these studies whether the observed changes in biological activity resulted from direct effects at the IL-6/IL-6R binding interface or, alternatively, from a gross perturbation of the conformation of the molecule.…”
mentioning
confidence: 99%
“…IL-6 has been expressed in rabbit reticulocyte lysate (Geiger et al, 1988), Escherichia coli (Brakenhoff et al, 1987;Tonouchi et al, 1988;Kriittgen et al, 1990a;Yasueda et al, 1990;Arcone et al, 1991a;Grennet et al, 1991;Zhang et al, 1992;Hammacher et al, 1994), Saccharomyces cerevisiae (Guisez et al, 1991), Pichia pastoris (this laboratory, unpublished data), Aspergillus nidulans , Xenopus laevis (Fontaine et al, 1991), baculovirus insect cells and Chinese hamster ovary (CHO) cells (Eisenthal et al, 1993;Orita et al, 1994).…”
Section: Post-translational Modifications Of Recombinant Il-6mentioning
confidence: 99%
“…Circular dichroism spectroscopy was used to show that recombinant IL-6 has a high a-helix content. The secondary structural compositions of human and mouse IL-6 expressed in E. coli are predicted to be 67% a-helix, 15% /?-sheet, 18% /?-turn and random coil (Kriittgen et al, 1990a), and 52% a-helix, 10% p-sheet, 19% p-turn and 19% random coil (Zhang et al, 1992), respectively. Estimations of the thermostability of IL-6 at physiological pH are hampered by the non-two-state equilibrium unfolding under these conditions.…”
Section: Physicochemical Characterization Of Il-6mentioning
confidence: 99%
“…Epitope mapping studies of hIL-6 have shown that neutralizing monoclonal antibodies against hIL-6 were directed toward the N-and C-terminal regions of IL-6, suggesting that these regions are in close proximity (Brakenhoff et al, 1990) and that residues 153-162 are important for biological activity on human cells (Ida et al, 1989). More direct evidence implicating the C-terminal region in receptor binding was obtained by site-directed mutagenesis studies (Nishimura et al, 1991Yasueda et al, 1992;Li et al, 1993;Savino et al, 1993), from deletion mutants (Kriittgen et al, 1990;Fontaine et al, 1993), and from murinelhuman IL-6 chimeras (Fiorillo et al, 1992a;Van Dam et al, 1993). By contrast, the N-terminal 28 amino acid residues of hIL-6 can be deleted without loss of biological activity (Brakenhoff et al, 1989).…”
mentioning
confidence: 99%